Should we suspect primary aldosteronism in patients with hypokalaemic rhabdomyolysis? A systematic review - Díaz-López, Everardo Josué; Villar-Taibo, Rocio; Rodriguez-Carnero, Gemma; Fernandez-Pombo, Antia; Garcia-Peino, Roberto; Blanco-Freire, Manuel Narciso; Pena-Dubra, Alberto; Prado-Moraña, Teresa; Fernández-Xove, Irea-; Pérez-Béliz, Edurne; Cameselle-Teijeiro, Jose Manuel; Hermida-Ameijeiras, Alvaro; et al. (Frontiers in Endocrinology, 2023)
Severe hypokalaemia causing rhabdomyolysis (RML) in primary aldosteronism (PA) is a rare entity and only a few cases have been reported over the last four decades. This systematic review and a case report aim to gather all published data regarding a hypokalaemic RML as presentation of PA, in order to contribute to the early diagnosis of this extremely rare presentation. Using PubMed Central, EMBASE and Google Scholar, a thorough internet-based search of the literature was conducted to identify articles and cases with RML secondary to hypokalaemia due to PA between June 1976 and July 2023. The case study concerns a 68-year-old male patient with hypokalaemic RML at presentation of PA. In the systematic review of the literature, 37 cases of RML secondary to hypokalaemia due to PA have been reported to date. In summary, median age was 47.5 years; the This is a provisional file, not the final typeset article male/female ratio was 17/21; all patients presented symptoms (weakness and/or myalgia); all the patients were hypertensive and only four patients had complications with acute renal failure (AKI). Although PA rarely presents with RML, it should be suspected when marked hypokalaemia and hypertension are also present. Early detection and management are essential to reduce the frequency of manifestations such as AKI.